2020
DOI: 10.1016/j.jval.2020.04.1000
|View full text |Cite
|
Sign up to set email alerts
|

Pnd110 Symptoms, Delayed Diagnosis and Quality of Life (Qol) Deterioration - Exploring the Burden of Amyotrophic Lateral Sclerosis (Als)

Abstract: Objectives: To understand the economic and humanistic burden attributed to myasthenia gravis (MG). Methods: We conducted a literature search (January 2009 to April 2019) in the biomedical database Embase (including Medline), focusing on English language observational studies and economic models evaluating patients with MG in the United States. Key search terms focused on costs, healthcare resource utilization, and quality of life (QoL). Results: A total of 18 studies were identified that included economic or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the recent systematic review of QoL deterioration in ALS by Forsythe and colleagues [ 11 ], a severe decline in health status and HRQoL was found to correlate with increased disease severity, with EQ-5D utility values ranging from 0.79 to 0.65 at stage 1, 0.67–0.53 at stage 2, 0.71–0.35 at stage 3, and 0.50–0.12 at stage 4 on the King’s staging system [ 30 , 45 47 ]. The results of the present investigation, with adjusted mean EQ-5D-5L utility scores ranging from 0.65 at King’s stage 1 to 0.11 at stage 4, are therefore in line with previous findings of QoL changes in pALS and are well below general population norms in the UK and other countries (0.83–0.92) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the recent systematic review of QoL deterioration in ALS by Forsythe and colleagues [ 11 ], a severe decline in health status and HRQoL was found to correlate with increased disease severity, with EQ-5D utility values ranging from 0.79 to 0.65 at stage 1, 0.67–0.53 at stage 2, 0.71–0.35 at stage 3, and 0.50–0.12 at stage 4 on the King’s staging system [ 30 , 45 47 ]. The results of the present investigation, with adjusted mean EQ-5D-5L utility scores ranging from 0.65 at King’s stage 1 to 0.11 at stage 4, are therefore in line with previous findings of QoL changes in pALS and are well below general population norms in the UK and other countries (0.83–0.92) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical impairment and progression rate of physical deterioration in ALS have a significant impact on emotional well-being and there is a correlation between disease severity and/or decreasing physical function and declining health-related quality of life (HRQoL) [ 9 , 10 ]. A recent systematic literature review investigating the burden of ALS confirmed that pALS experienced poor QoL and loss of function, which deteriorated with disease progression [ 11 ]. The burden of symptoms was high, with patients experiencing various debilitating symptoms, with fatigue, depression, and pain being the most frequently reported [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations